Charles S. Peirce and the Neglected Argument for the Reality of God - Nubiola, Jaime (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper aims, above all, to invite a direct reading of the article that Charles S. Peirce published in 1908 with the title “A Neglected Argument for the Reality of God.” More than a century after its original publication, that article by Peirce has not lost its relevance: its careful reading continues to provide a lot to think about. To this end, my presentation is organized in six sections: 1) introduction; 2) presentation of “A Neglected Argument for the Reality of God”; 3) the notion of reality; 4) the heart of the “Neglected Argument”; 5) contemporary discussion: a response to Oya (2021); and 6) conclusion.